2007
DOI: 10.1111/j.1365-2958.2007.05859.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of both MAP kinases of the human malaria parasite Plasmodium falciparum by reverse genetics

Abstract: SummaryThe kinome of the human malaria parasite Plasmodium falciparum includes two genes encoding mitogen-activated protein kinase (MAPK) homologues, pfmap-1 and pfmap-2, but no clear orthologue of the MAPK kinase (MAPKK) family, raising the question of the mode of activation and function of the plasmodial MAPKs. Functional studies in the rodent malaria model Plasmodium berghei recently showed the map-2 gene to be dispensable for asexual growth and gametocytogenesis, but essential for male gametogenesis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 43 publications
(68 reference statements)
3
107
1
7
Order By: Relevance
“…The P. falciparum p52 Ϫ and p36 Ϫ phenotypes are therefore similar to the phenotypes observed for the corresponding rodent malaria knockouts (11,12). Such experimental concurrence of phenotypes between rodent malaria parasite mutants and P. falciparum mutants is important because it has been observed that knockout of orthologous genes in rodent and human malaria parasites can result in distinct phenotypes (33,34).…”
Section: Discussionmentioning
confidence: 49%
“…The P. falciparum p52 Ϫ and p36 Ϫ phenotypes are therefore similar to the phenotypes observed for the corresponding rodent malaria knockouts (11,12). Such experimental concurrence of phenotypes between rodent malaria parasite mutants and P. falciparum mutants is important because it has been observed that knockout of orthologous genes in rodent and human malaria parasites can result in distinct phenotypes (33,34).…”
Section: Discussionmentioning
confidence: 49%
“…Among these 22 ePKs are 8 enzymes that we previously reported as playing a crucial role in asexual proliferation: Pfmap-2 (PF11_0147) 9 , Pfnek-1 (PFL1370w) 10 , PfCK2 (PF11_ 0096) 11 , PfTKL3 (PF13_0258) 12 , Pfcrk-3 (PFD0740w) 13 , PfCLK1 (PF14_0431) 14 , PfCLK2 (PF14_0408) 14 and PfARK1 (PF13_0258) 15 . Others have provided reverse genetics evidence for essentiality of three additional ePKs, PfCDPK1 (PFB0815w) 16 , PfPKG (PF14_ 0346) 17 and PfPCDPK5 (PF13_0211) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Typically, this signal transduction pathway is formed by three or four protein kinases associated with distinct ePK families: MAP4K or MEKKK (a tyrosine-like kinase such as Raf, or a member of the STE20 family), MAP3K or MEKK (a member of the STE11 family), MAPKK or MEK (a STE7 member) and MAPK family (best characterized in the ERK1/ERK2, p38 and JNK subfamilies) [84]. However, in Plasmodium and most other apicomplexans, the STE group of kinases is reduced to one or two distantly related members, or even missing entirely [85], although two clear (but atypical) members of the MAPK family are present [86]. One of these, Pfmap-1, has been demonstrated to be phosphorylated on the conserved TXY motif in its activation loop [20], while this otherwise highly conserved activation motif is substituted in the other MAPK (Pfmap-2) by TSH [44]; no evidence for in vivo phosphorylation of this TSH motif is available, but mutating either the Thr or the His (but not the Ser) dramatically affects kinase activity of the recombinant enzyme [44].…”
Section: !)mentioning
confidence: 99%